Targeting Multiresistant Gram-Positive Bacteria by Ruthenium, Osmium, Iridium and Rhodium Half-Sandwich Type Complexes With Bidentate Monosaccharide Ligands - Balázs, Bence; Tóth, Zoltán; Kacsir, István; Sipos, Adrienn; Buglyó, Péter; Somsák, László; Bokor, Éva; Kardos, Gábor; Bai, Péter (Frontiers in Chemistry, 2022)
Bacterial resistance to antibiotics is an ever-growing problem in heathcare. We have previously identified a set of osmium(II), ruthenium(II), iridium(III) and rhodium(III) half-sandwich type complexes with bidentate monosaccharide ligands possessing cytostatic properties against carcinoma, lymphoma and sarcoma cells with low micromolar or submicromolar IC50 values. Importantly, these complexes were not active on primary, non-transformed cells. These complexes have now been assessed as to their antimicrobial properties and found to be potent inhibitors of the growth of reference strains of Staphylococcus aureus and Enterococcus faecalis (Gram-positive species), though the compounds proved inactive on reference strains of Pseudomonas aerugonisa, Escherichia coli, Candida albicans, Candida auris and Acinetobacter baumannii (Gram-negative species and fungi). Furthermore, clinical isolates of Staphylococcus aureus and Enterococcus sp. (both multiresistant and susceptible strains) were also susceptible to the organometallic complexes in this study with similar MIC values as the reference strains. Taken together, we identified a set of osmium(II), ruthenium(II), iridium(III) and rhodium(III) half-sandwich type antineoplastic organometallic complexes which also have antimicrobial activity among Gram-positive bacteria. These compounds represent a novel class of antimicrobial agents that are not detoxified by multiresistant bacteria suggesting a potential to be used to combat multiresistant infections.